Biocontrol of pests in apples under integrated fruit production - Shaw, P.W.; Wallis, D.R. (New Zealand Plant Protection, 2008)
The biological control of some key orchard pests achieved within an Integrated Fruit Production (IFP) apple block was assessed Insecticide sprays were used to manipulate the numbers of natural enemies Treatments included applications of the broadspectrum insecticide carbaryl a selective insecticide programme (IFP) and a control (no insecticides) Plots treated with carbaryl became heavily infested with woolly apple aphid and European red mite However carbaryl sprays did not completely prevent lacewings ladybirds and the woolly apple aphid parasitoid Aphelinus mali subsequently moving into the plots in response to the high host populations Numbers of some natural enemies were reduced in the carbaryl treatment and the trees were damaged by mites and woolly apple aphids The selective and noinsecticide programmes did not disrupt natural enemies and pest levels in trees and fruit were similar and acceptable